2020
DOI: 10.2147/dddt.s261027
|View full text |Cite
|
Sign up to set email alerts
|

<p>Assessment of a New Ginsenoside Rh2 Nanoniosomal Formulation for Enhanced Antitumor Efficacy on Prostate Cancer: An in vitro Study</p>

Abstract: Introduction: Ginsenoside Rh2, purified from the Panax ginseng root, has been demonstrated to possess anticancer properties against various cancerous cells including colorectal, breast, skin, ovarian, prostate, and liver cancerous cells. However, the poor bioavailability, low stability on gastrointestinal systems, and fast plasma elimination limit further clinical applications of Ginsenoside Rh2 for cancer treatments. In this study, a novel formulation of niosomal Ginsenoside Rh2 was prepared using the thin fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 41 publications
(55 reference statements)
0
10
0
Order By: Relevance
“…For this reason, Zare-Zardini et al [54] loaded GRH2 into the lipophilic bilayer of LP, and the inclusion rate reached 93.5%. The anticancer study involving the PC3 prostate cancer cell line showed that the administration of GRH2 in the form of LP enhanced the cytotoxic activity of PC3 prostate cancer cell line cells compared with free GRH2 solution (IC 50 values 31.2 vs. 62.7 μg/ mL) [54]. The content of GRH2 in ginseng root is extremely low [139].…”
Section: Ginsenoside Rh2 (Grh2)mentioning
confidence: 99%
“…For this reason, Zare-Zardini et al [54] loaded GRH2 into the lipophilic bilayer of LP, and the inclusion rate reached 93.5%. The anticancer study involving the PC3 prostate cancer cell line showed that the administration of GRH2 in the form of LP enhanced the cytotoxic activity of PC3 prostate cancer cell line cells compared with free GRH2 solution (IC 50 values 31.2 vs. 62.7 μg/ mL) [54]. The content of GRH2 in ginseng root is extremely low [139].…”
Section: Ginsenoside Rh2 (Grh2)mentioning
confidence: 99%
“…e preparation of ginsenoside Rh2 chitosan tripolyphosphate (CS-RH2-TPP) nanoparticles (NPs) was carried out by referring to the study of Zare-Zardini et al [19]. CS (4 mg, Shandong AK Biotech Co., Ltd., China) was stirred in 1% acetic acid (4 mL, Sigma-Aldrich, Merck KGaA) until it was completely dissolved, and then, the PH was adjusted to 5 with 2 mol/L NaOH.…”
Section: Preparation Of Cs Npsmentioning
confidence: 99%
“…OVCAR-3 cell wase then rinsed with PBS three times, and they were xed with 4%, paraformaldehyde solution (Sigma, USA). Lastly, the cell incubation was performed with DAPI solution for 15 min, and a uorescence microscope was employed for imaging the cells (20,24,28).…”
Section: Nanocarrier Uptake Surveysmentioning
confidence: 99%